THE CORRELATION BETWEEN CELL OF ORIGIN SUBTYPE WITH OVERALL SURVIVAL OF DIFFUSE LARGE B-CELL LYMPHOMA PATIENTS IN KARIADI GENERAL HOSPITAL SEMARANG - Jenifer Marsela Tarius; Hermawan Istiadi; Ika Pawitra Miranti; Intan Rahmania Eka Dini (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: DLBCL is the most common type of NHL in the world. DLBCL based on cell of origin is divided into GCB and non-GCB. The diagnosis of DLBCL has not been routinely done to its cell of origin, and there have not been many studies that discuss the DLBCL subtype and the overall survival of the patients, especially in Kariadi General Hospital. This study aims to determine the correlation of DLBCL cell of origin with the 2-year overall survival of DLBCL patients in Kariadi General Hospital. Methods: This is an observational analytic study of 40 DLBCL patients in Kariadi General Hospital from January to August 2017. The data collection including: age of diagnosis, location, stage and 2-year overall survival. Data analysis used chi square test and Kaplan Meier curve. Results: GCB patients had higher 2-year overall survival than non-GCB subtype significantly (p: 0.047), with a 2-year survival rate of GCB subtype was 66.7% and non-GCB subtype was 31.6%. GCB patients tend to have early stage than non-GCB subtype significantly (p:0.028). Conclusion: DLBCL GCB subtype patients had significantly higher 2-year overall survival therefore it has better prognosis than non-GCB subtype.